2014
DOI: 10.1115/1.4028326
|View full text |Cite
|
Sign up to set email alerts
|

Blade Tip Carving Effects on the Aerothermal Performance of a Transonic Turbine

Abstract: Tip leakage flows in unshrouded high speed turbines cause large aerodynamic penalties, induce significant thermal loads and give rise to intense thermal stresses onto the blade tip and casing endwalls. In the pursuit of superior engine reliability and efficiency, the turbine blade tip design is of paramount importance and still poses an exceptional challenge to turbine designers. The ever-increasing rotational speeds and pressure loadings tend to accelerate the tip flow velocities beyond the transonic regime. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…The rotor disk was divided into seven sectors, each presenting 6-7 blades of equal tip geometry to ensure flow periodicity and all sharing the same baseline blade profile. The alternative blade tip designs were obtained from a previous optimization effort [20,21]. The paper presents the aerodynamic performance of two optimized profiles, a squealer-like rimmed geometry (AC06D) and a contoured tip (AC07T), in comparison to a baseline conventional squealer tip (IN01D) ( Figure 1c).…”
Section: Test Articlementioning
confidence: 99%
“…The rotor disk was divided into seven sectors, each presenting 6-7 blades of equal tip geometry to ensure flow periodicity and all sharing the same baseline blade profile. The alternative blade tip designs were obtained from a previous optimization effort [20,21]. The paper presents the aerodynamic performance of two optimized profiles, a squealer-like rimmed geometry (AC06D) and a contoured tip (AC07T), in comparison to a baseline conventional squealer tip (IN01D) ( Figure 1c).…”
Section: Test Articlementioning
confidence: 99%
“…A first approach used a 48 control-points Bezier surface mapped onto the blade top surface to create smoothly contoured tip shapes. This design strategy, particularly suited for transonic blades operating at tight clearances, allows a substantial limitation of the tip heat transfer by controlling the acceleration of the tip flows beyond sonic conditions [28]. The second optimization employed a topology-like strategy to enable the design of arbitrary squealer-like tip seals [29].…”
Section: New Blade Tip Geometriesmentioning
confidence: 99%
“…De Maesschalck et al. 27,28 conducted several studies concerning the blade tip carving influence on the aerothermal performance. The investigations indicated that the aerodynamic performance and heat transfer requirement should be balanced to obtain the optimal carving tip.…”
Section: Introductionmentioning
confidence: 99%